miR-22 inhibits the proliferation, motility, and invasion of human glioblastoma cells by directly targeting SIRT1 - Chen, Hanchun; Lu, Qiong; Fei, Xifeng; Shen, Likui; Jiang, Dongyi; Dai, Dongwei (Tumor biology, 2016)
Recently, microRNAs (miRNAs), a kind of small and non-coding RNA, can target the downstream molecules. Increasing evidence demonstrates that miRNAs meditate the onset and progression of a variety of tumors. In the present study, we carried out gene transfection, western blot, and reverse transcription PCR (RT-PCR) to explore the role of miR-22 in glioblastoma tissues and cell lines. Here, we verified that the expression of miR-22 was downregulated in glioblastoma tissues and cells rather than matched non-tumor tissues and normal human astrocyte (NHA) cells ( p < 0.001). By contrast, SIRT1 messenger RNA (mRNA) and protein were upregulated in glioblastoma tissues and cells ( p < 0.001). In vitro miR-22 mimics interfered with cell proliferation, migration, and invasion of U87 and U251 cells. Mechanically, the 3′-untranslated regions (3′-UTRs) of SIRT1 were a direct target of miR-22, leading to the decreased expression of SIRT1 protein in U87 and U251 cells. Meanwhile, miR-22 mimics also inhibited the expression of epidermal growth factor receptor (EGFR) and matrix metallopeptidase 9 (MMP9). In conclusion, miR-22 inhibited cell proliferation, migration, and invasion via targeting the 3′-UTR of SIRT1 in the progression of glioblastoma and miR-22-SIRT1 pathway can be recommended as a potential target for treatment of glioblastoma.